2023
DOI: 10.1038/s41467-023-38437-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial metabolomics reveals glycogen as an actionable target for pulmonary fibrosis

Abstract: Matrix assisted laser desorption/ionization imaging has greatly improved our understanding of spatial biology, however a robust bioinformatic pipeline for data analysis is lacking. Here, we demonstrate the application of high-dimensionality reduction/spatial clustering and histopathological annotation of matrix assisted laser desorption/ionization imaging datasets to assess tissue metabolic heterogeneity in human lung diseases. Using metabolic features identified from this pipeline, we hypothesize that metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…1H). Consistent with previous reports[16, 31, 32], gene set variation analysis (GSVA) demonstrated that the upregulation of N -Glycan biosynthesis, glycosaminoglycan biosynthesis, arginine and proline metabolism are associated with pulmonary fibrosis (Fig. 1D).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1H). Consistent with previous reports[16, 31, 32], gene set variation analysis (GSVA) demonstrated that the upregulation of N -Glycan biosynthesis, glycosaminoglycan biosynthesis, arginine and proline metabolism are associated with pulmonary fibrosis (Fig. 1D).…”
Section: Resultssupporting
confidence: 91%
“…3A). To further investigate the role of TREM2 in IPF patients, a single-cell RNA Seq dataset of lung samples from three healthy controls and three IPF patients (GSE128033) [31] in GEO public platform was analyzed. After quality control and filtering, we obtained 19,012 cells (3,626 cells from control lungs and 15,386 cells from IPF lungs) for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, 6-and 12-month-old mice showed increased hypoactivity, decreased motility time and mean velocity; however, the difference in 12-month-old YAC128 was higher (Figure 1). MALDI-MSI technology makes it possible to preserve the cellular, molecular and spatial integrity of tissues, along with region-specific alterations that may be lost during the homogenisation process (Baijnath et al, 2022;Conroy et al, 2023;Franck et al, 2009). Using the MALDI-MSI system, which enables to detect the expression changes of proteins without losing their spatial location, we determined that the intensity levels of 89, 83 and 82 proteins were significantly different in YAC128 versus their control mice at the pre-stage, mild stage and pathological stage, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-MSI combines the accuracy and sensitivity of mass spectrometry with added spatial information and glycogen architecture (Conroy et al, 2023;Young et al, 2022).…”
Section: B R Ain G Lycog En -De Tec Ti On and Loc Aliz Ationmentioning
confidence: 99%